β(1)-, β(2)- and atypical β-adrenoceptor-mediated relaxation in rat isolated aorta - Brawley, L (2000)
1. β-adrenoceptor-mediated relaxation was investigated in ring preparations of rat isolated thoracic aorta. Rings were pre-constricted with a sub-maximal concentration of noradrenaline (1 μM) and relaxant responses to cumulative concentrations of β-adrenoceptor agonists obtained. 2. The concentration-response curve (CRC) to isoprenaline was shifted to the right by propranolol (0.3 μM) with a steepening of the slope. Estimation of the magnitude of the shift from EC(50) values gave a pA(2) of 7.6. Selective β(1)- and β(2)-adrenoceptor antagonists, CGP 20712A (0.1 μM) and ICI 118551 (0.1 μM), respectively, produced 4 and 14 fold shifts of the isoprenaline CRC. 3. Atypical β-adrenoceptor agonists also produced concentration-dependent relaxation of aortic rings. The order of potency of the β-adrenoceptor agonists was (−log EC(50)): isoprenaline (6.25)>cyanopindolol (5.59)>isoprenaline+propranolol (5.11)>CGP 12177A (4.40)>ZD 2079 (4.24)>ZM 215001 (4.07)>BRL 37344 (3.89). Relaxation to CGP 12177A and ZM 215001 was unaffected by propranolol (0.3 μM). 4. SR 59230A (⩽1 μM) and cyanopindolol (1 μM), β(3)-adrenoceptor antagonists, had no effect on the isoprenaline (in the presence of propranolol) or CGP 12177A CRCs. Bupranolol and CGP 20712A, at μM concentrations (β(4)-adrenceptor antagonists), inhibited responses to isoprenaline (in the presence of propranolol) and CGP 12177A. 5. In conclusion, atypical β-adrenoceptors co-exist with β(1)- and β(2)-adrenoceptors in rat aorta. Although non-conventional partial agonists and selective β(3)-adrenoceptor agonist cause relaxation, the vascular atypical β-adrenoceptor does not appear to correspond to the β(3)-adrenoceptor. There are, however, similarities with the putative β(4)-adrenoceptor.